Service-driven traffic engineering for intradomain quality of service management. - Trimintzios, P. (IEEE Network : the magazine of global information exchange)
Quality of service delivery in IP networks is an important area for service providers, pointing to new business opportunities for premium quality traffic. While there has been relevant research on traffic engineering for QoS management, the problem has never been addressed through a holistic approach that brings together service management and traffic engineering. We present an integrated approach to intradomain QoS management that brings together two-level service management and traffic engineering approaches, coupled through the concept of the resource provisioning cycle. We present validation results for MPLS-based traffic engineering through both testbed experimentation and simulation; we also present validation results for monitoring through testbed experimentation. The article updates, enhances, and validates the top-level view of this integrated architecture presented in our earlier paper (see Trimintzios, P. et al., IEEE Commun. Mag., vol.39 no.5, 2001).